Study on the Effect of Shifting ‘Zero’ in Output Membership Function on Fuzzy Logic Controller of the ROV using Micro-box Interfacing - Ab Azis, Fadilah; Mohd Aras, Mohd Shahrieel; Ali, Fara Ashikin; Othman, Muhammad Nur; Abdullah, Shahrum Shah; Lim , Wee Teck; Lee, Dai Cong (2014)
This paper investigates the study on the effect of shifting ‘zero’ membership function on Fuzzy Logic Controller (FLC) design of underwater Remotely Operated Vehicle (ROV) for depth control using Microbox 2000/2000C interfacing based on thruster system. The issues occurred with a ROV design is where the thruster system can easily drain up current from the supply (e.g. battery source or power bank) and this will limit time to using the ROV. FLC do not have a rigid approach to tune it and may cause the process of tuning will be highly time costing. Therefore, a simple method by a study on the effect of shifting zero membership function will act as a one technique to tune the FLC for future references. The ROV Trainer will be developed to test the proposed control method using Microbox 2000/2000C. The ROV Trainer consists of aluminum box, thrusters, drivers, interface connector, and etc and interfacing with Microbox act as microcontroller. Fuzzy logic toolbox in MATLAB will be used to study the shifting zero membership function so that the effect of the adjustment can be investigated. The result of this project shows that, by shifting zero membership function of the fuzzy logic controller, the performance of the fuzzy logic controller is normally improved.